Application of forensic accounting techniques in the South African banking industry for the purpose of fraud risk mitigation - Oluwatoyin Esther Akinbowale; Heinz Eckart Klingelhöfer; Mulatu Fekadu Zerihun (Cogent Economics & Finance, 2023)
The purpose of this study is to investigate the application of forensic accounting techniques in relation to fraud risk mitigation. This study employed an explanatory research design and a qualitative approach accompanied with a purposive sampling method. A primary data source was devised with a focus on the 17 licensed commercial banks registered in South Africa. By obtaining a true reflection of the situations in the banks, a conclusion was drawn following the outcome of the inferential statistical analysis. The research was conducted at the individual and organisational levels, with the bank consultants presenting their views. One hypothesis was formulated and non-parametric statistical analyses involving the use of Chi-square test, Fisher's Exact test and Spearman's correlation were carried out. The results obtained substantiate that the loopholes created as a result of non-effective application of forensic techniques are partly responsible for some cyberfraud incidents in the banking industry. There is no sufficient evidence to ascertain whether the fraud risk assessment and management in the banking industry has a relationship with the effective application of forensic accounting techniques in terms of the identified causes of cyberfraud. However, the findings establish a positive correlation between fraud risk assessment and management as it relates to forensic accounting implementation. This study provides an insight into the significance of forensic accounting applications for fraud risk mitigation. There is still a death of information regarding the forensic accounting for fraud risk mitigation; hence, it is envisaged that this study will add to the existing literature in this regard.
Keywords: 330; Cyberfraud; Forensic accounting; Information security; Management control systems